A first immunohistochemistry study of transketolase and transketolase-like 1 expression in canine hyperplastic and neoplastic mammary lesions. Issue 1 (December 2016) - Burrai, Giovanni; Tanca, Alessandro; Cubeddu, Tiziana; Abbondio, Marcello; Polinas, Marta; Addis, Maria; Antuofermo, Elisabetta
Abstract Background Canine mammary tumors represent the most common neoplasm in female dogs, and the discovery of cancer biomarkers and their translation to clinical relevant assays is a key requirement in the war on cancer. Since the description of the 'Warburg effect', the reprogramming of metabolic pathways is considered a hallmark of pathological changes in cancer cells. In this study, we investigate the expression of two cancer-related metabolic enzymes, transketolase (TKT) and transketolase-like 1 (TKTL1), involved in the pentose phosphate pathway (PPP), an alternative metabolic pathway for glucose breakdown that could promote cancer by providing the precursors and energy required for rapidly growing cells. Results TKT and TKTL1 protein expression was investigated by immunohistochemistry in canine normal (N  = 6) and hyperplastic glands (N  = 3), as well as in benign (N  = 11) and malignant mammary tumors (N  = 17). TKT expression was higher in hyperplastic lesions and in both benign and malignant tumors compared to the normal mammary gland, while TKTL1 levels were remarkably higher in hyperplastic lesions, simple adenomas and simple carcinomas than in the normal mammary glands (P <0.05 ). Conclusions This study reveals that the expression of a key PPP enzyme varies along the evolution of canine mammary neoplastic lesions, and supports a role of metabolic changes in the development of canine mammary tumors.